(untitled) - Pearson, Malcolm (London, 2004)
The Reed's Skipper's Handbook, now in its 4th edition, has been a bestseller since first publication. A handy pocket size it is an aide-memoire of everything a boater would need to know at sea. Packed with a wide range of information in a concise form it is frequently recommended by Yachtmaster Instructors as a quick reference guide and as a revision aid for anyone taking their Dayskipper and Yachtmaster certificates. The 4th edition has been updated and reorganised to make it even easier for the reader to navigate right to the information they want. A must for anyone going to sea in any size boat - be they novice or old hand.
Keywords: Nghề hàng hải,Du lịch bằng thuyền,Navigation,Boats and boating